2011
DOI: 10.1002/bin.339
|View full text |Cite
|
Sign up to set email alerts
|

Response Interruption and Differential Reinforcement of Alternative Behavior for the Treatment of Pica

Abstract: Pica displayed by two individuals with autism was decreased by a treatment involving differential reinforcement and response interruption that altered the chain of behavior involved in pica (i.e., picking up items and placing them in the mouth). The treatment involved establishing prompts to 'clean-up' as a new discriminative stimulus (SD) for picking up items from the floor; and holding potential pica items was established as an SD for discarding those items in a trash receptacle, putting them away, or using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 22 publications
(37 reference statements)
2
41
0
Order By: Relevance
“…The sixth participant's pica was maintained by social‐positive reinforcement (access to attention) only. Past research on the evaluation and treatment of pica has demonstrated that pica is often maintained by automatic reinforcement (Hagopian et al, ; McCord et al, ; Piazza et al, ; Piazza et al, ; Winton & Singh, ). One notable exception was the Piazza et al () study, in which the researchers determined that one of the three participants in that study engaged in pica maintained by both automatic reinforcement and social‐positive reinforcement (access to tangibles), whereas a second participant engaged in pica maintained only by social‐positive reinforcement (access to attention).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sixth participant's pica was maintained by social‐positive reinforcement (access to attention) only. Past research on the evaluation and treatment of pica has demonstrated that pica is often maintained by automatic reinforcement (Hagopian et al, ; McCord et al, ; Piazza et al, ; Piazza et al, ; Winton & Singh, ). One notable exception was the Piazza et al () study, in which the researchers determined that one of the three participants in that study engaged in pica maintained by both automatic reinforcement and social‐positive reinforcement (access to tangibles), whereas a second participant engaged in pica maintained only by social‐positive reinforcement (access to attention).…”
Section: Discussionmentioning
confidence: 99%
“…For example, LeBlanc, Piazza, and Krug () demonstrated that blocking (i.e., immediately before the item passed the plane of the lips) was as effective as restraint in reducing pica. In addition, blocking often is included in treatment packages for pica, such as interrupting pica attempts and prompting a more appropriate behavior (Goh, Iwata, & Kahng, ; Hagopian, Gonzalez, Rivet, Triggs, & Clark, ; Ricciardi, Luiselli, Terrill, & Reardon, ; Schmidt et al, ; Slocum, Mehrkam, Peters, & Vollmer, ). For example, Hagopian et al used response blocking, as well as differential reinforcement of alternative behavior, to decrease automatically maintained pica by two teenagers.…”
mentioning
confidence: 99%
“…In the behavioral assessment of pica, most researchers have found that the behavior is partially if not completely maintained by automatic reinforcement (Ing, Roane, & Veenstra, ; Mace & Knight, ; Piazza, Hanley, & Fisher, ; Piazza et al, ; Rapp, Dozier, & Carr, ). It is possible that because automatically reinforced behavior is difficult to extinguish and alternative reinforcers would have to compete with the automatic reinforcement produced by the pica itself, some reinforcement procedures alone have not been effective at reducing pica (Finney, Russo, & Cataldo, ; Fisher et al, ; Hagopian, Gonzalaz, Rivet, Triggs, & Clark, ). Treatments for pica have also involved punishment‐based procedures such as overcorrection (Foxx & Martin, ; Matson, Stephens, & Smith, ; Mulick, Barbour, Schroeder, & Rojahn, ) and contingent aversive taste (Ferreri, Tamm, & Wier, ).…”
Section: Introductionmentioning
confidence: 99%
“…Differential reinforcement has also been used as a treatment for pica. The alternative responses have included: The subject having his hands busy (Smith, ), chewing gum (Donnelly & Olczak, ), exchanging the pica item (Carter, ; Goh et al, ; Hagopian et al, ; Kern, Starosta, & Adelman, ), or discarding the pica item (Ricciardi, Luiselli, Terrill, & Reardon, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation